Effect of Genetic Type and Sex on Reproductive, Growth, Survival Performance and Thermal Tolerance Index of the Local Chicken (Gallus gallus) of the Western Highlands of Cameroon - Keambou , T.C.; Hako, B.A.; Bembide, C.; Emma, P.J. Ngono; Manjeli, Y. (International Journal of Poultry Science, 2013)
Reproductive performance of local chicken from the Western Highlands of Cameroon has been significantly influenced by the genetic type, the naked neck chicken displaying the best laying performance. Fertility rate was higher (P